2013
DOI: 10.1167/iovs.12-10948
|View full text |Cite
|
Sign up to set email alerts
|

Copy Number Variations of DNA Repair Genes and the Age-Related Cataract: Jiangsu Eye Study

Abstract: PURPOSE. DNA damage is critical in the pathogenesis of agerelated cataract (ARC). This study examined the association of copy number variations (CNVs) of DNA repair genes with susceptibility to ARC in the Han Chinese.METHODS. Study participants were from the population-based Jiangsu Eye Study, which includes 780 ARC patients and 525 controls. DNA was extracted from blood for copy number (CN) assays using RT-PCR. The Comet assay was to assess DNA damage in peripheral lymphocytes. RESULTS.Novel CNV was detected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…The decrease in oxidative damage associated with exercise training could be explained by an increase in antioxidant and metabolic efficiency, which possibly prevent the stimulation of DNA repair enzyme activity. These results enhance the importance of regular exercise in the prevention of DNA damage accumulation which has been related to aging (Nalapareddy et al 2008) and some agerelated diseases including: cardiovascular disease (Collins et al 1998), diabetes mellitus (HannonFletcher et al 2000), cataracts (Jiang et al 2013;Su et al 2013), and several cancers (Malins et al 2001;Akcay et al 2003;Peddireddy et al 2012). In addition, it should be noted that DNA damage depends on a complex system which is not thoroughly understood.…”
Section: Discussionmentioning
confidence: 87%
“…The decrease in oxidative damage associated with exercise training could be explained by an increase in antioxidant and metabolic efficiency, which possibly prevent the stimulation of DNA repair enzyme activity. These results enhance the importance of regular exercise in the prevention of DNA damage accumulation which has been related to aging (Nalapareddy et al 2008) and some agerelated diseases including: cardiovascular disease (Collins et al 1998), diabetes mellitus (HannonFletcher et al 2000), cataracts (Jiang et al 2013;Su et al 2013), and several cancers (Malins et al 2001;Akcay et al 2003;Peddireddy et al 2012). In addition, it should be noted that DNA damage depends on a complex system which is not thoroughly understood.…”
Section: Discussionmentioning
confidence: 87%
“…13 Previously, we reported that polymorphisms and copy number variations of some DNA repair genes, such as Werner syndrome protein (WRN), are involved in ARC pathogenesis, but two SNPs in OGG1 (rs2072668 and rs2304277) were not associated with an increased risk of ARC. 14,15 DNA methylation is an important epigenetic mechanism in gene regulation and is usually associated with transcriptional silencing of genes without alteration of the DNA sequence. Methylation at the C5 position of cytosine is a common epigenetic modification, and cytosine methylation in CpG dinucleotides can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies have detected DNA damage of peripheral lymphocytes by comet assay in ARC patients from a population-based study. We found that DNA damage of peripheral lymphocytes was significantly higher in ARC patients and associated with DNA repair gene polymorphisms [11,13,14]. …”
Section: Introductionmentioning
confidence: 99%